A Multiple Component Intervention to Assist Young Pregnant Smokers to Cease Smoking: A Randomised Controlled Pilot Study - Lewis, Lucy; Hauck, Yvonne; Ronchi, Fiona; Allsop, Steve; Doherty, D. (2017)
Objective: Australian rates of cigarette smoking are the lowest in the world. Young pregnant smokers are a sub population where smoking remains high. This pilot study assessed the feasibility of a multi-component intervention (Carbon Monoxide testing, motivational interviewing and a non-smoking buddy) to assist young pregnant women to cease smoking. Methods: Between October 2013 and June 2015, this multi-centred West Australian study recruited pregnant smokers aged 16 to 24, attending their first antenatal visit. Women (n=80) were randomised to the intervention and standard smoking cessation advice (n=43) or standard smoking cessation advice alone (n=37). At 36 weeks gestation and six weeks post birth, cessation rates were compared between groups using repeated measures survival analysis and reduction in smoking was examined using repeated measures linear regression on the number of cigarettes smoked. Results: The majority (89%) of women were unemployed or not in education, used illicit drugs (43%) and had experienced sexual abuse (23%). Involvement with child protection services was common (38%). Cigarette initiation occurred at a mean age of 13 years, median number of cigarettes smoked at baseline was 10 in both groups. Smoking cessation in intervention and controls were 17% vs. 14% at 36 weeks and 23% vs. 7% 6 weeks post birth. No significant differences in cessation or smoking reduction between groups were found individually or in the repeated events analysis. Conclusion: Given the low number of participants our findings cannot conclusively rule out this multi-component intervention. We believe it remains possible this intervention may prove effective in a larger group of participants and in another setting. Monitoring trends in this vulnerable, difficult to engage group of pregnant young women is important if we are to continue to devise effective interventions.